Pathological, hematological and biochemical alteration in broiler chickens infected with mycotoxin in Babylon province - Hayder Abd AL-Emier Almremdhy; Ghusoon Abdul Kareem Neamha; Zina Bakir Al-Hilli; Rafal Jalil Awadh (Open Veterinary Journal)
Background: Mycotoxins considered one of the most important problems and threats that face the poultry producers.